Business Strategy Analysis at Warmindo "Warung Kedai Emak" - Siti Nurlela; Rayhan Vansuri; Febriyanti Febriyanti; Salza Rio Pratama; Rifqi Ramadhan; Jumawan Jumawan (Jurnal Akuntansi, Manajemen dan Bisnis Digital, 2023)
Food stalls or coffee shops have become an inseparable part of everyday life in Indonesian society. These establishments offer convenience and comfort to customers who want to enjoy delicious dishes or simply relax while sipping a cup of warm coffee. One of the well-known food stalls in the community is Warmindo "Warung Kedai Emak." This article will analyze the business strategies implemented by Warmindo "Warung Kedai Emak" based on research conducted through interviews with the owner. The study employed interview techniques and applied a descriptive method. Based on the research findings from the interview with the owner of Warmindo "Warung Kedai Emak," it can be concluded that the business strategy employed by this food stall involves a good understanding of customer preferences, selecting suppliers with competitive prices, adjusting product prices according to the market, effective inventory management, and future business development plans. These strategies have contributed to the success of Warmindo "Warung Kedai Emak" in the competitive industry. The information obtained through the interviews provides valuable insights for other food stall owners who seek to enhance their business performance.